2016
DOI: 10.1111/are.12971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary DHA/EPA ratios on growth performance, survival and fatty acid composition of juvenile swimming crab (Portunus trituberculatus)

Abstract: This study was conducted to investigate the effects of dietary docosahexaenoic to eicosapentaenoic acid (DHA/EPA) ratios on growth performance, survival and fatty acid composition of juvenile swimming crab (Portunus trituberculatus). Four isonitrogenous and isoenergetic experimental diets were formulated to contain different DHA/EPA ratios (0.70, 0.84, 1.06 and 1.25). There were three replicates (15 crabs per replicate) for each diet treatment. The crabs were fed (about 6-8% body weight) twice daily for 8 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…One approach to improve crab survival and production is to develop nutrient balanced and quality consistent feed. There already are some studies focus on nutritional requirements of juvenile swimming crab, such as dietary protein (Huo et al., ; Jin et al., ), dietary phospholipids (Li et al., ; Wang et al., ), dietary cholesterol (Han et al., ) and dietary DHA/EPA ratios (Hu et al., ). However, only a few nutritional studies for early life stage (Wang, Yang, Li, Wang, & Han, ).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to improve crab survival and production is to develop nutrient balanced and quality consistent feed. There already are some studies focus on nutritional requirements of juvenile swimming crab, such as dietary protein (Huo et al., ; Jin et al., ), dietary phospholipids (Li et al., ; Wang et al., ), dietary cholesterol (Han et al., ) and dietary DHA/EPA ratios (Hu et al., ). However, only a few nutritional studies for early life stage (Wang, Yang, Li, Wang, & Han, ).…”
Section: Introductionmentioning
confidence: 99%
“…Marine crustaceans have a limited capacity to synthesize n‐3 LC‐PUFA (such as DHA and EPA) to meet metabolic requirements, so they must obtain these fatty acids from diets (Hu et al, ). The results of present study showed that fatty acid composition in hepatopancreas and muscle reflected the dietary fatty acids profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have also been observed in some previous studies (Du et al, ; Li et al, ; Unnikrishnan, Chakraborty, & Paulraj, ). Moreover, numerous studies have shown that fatty acid composition of diets can alter hepatopancreas or muscle fatty acid composition in aquatic animals (Ding et al, ; Hu et al, ). The present study demonstrated that different dietary fatty acid profiles could impact on tissue fatty acid composition and biosynthesis in swimming crab, and further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Marine organisms with a wide biogeographic distribution that inhabit heterogeneous environments can show variations in the composition and profiles of fatty acids with latitude [ 35 , 36 ]. This variability in fatty acid profiles can result, for example, from variations in the essential fatty acids that are obtained through the organism’s diet and cannot be synthesized by the organism itself [ 31 , 37 , 38 ]. For instance, eicosapentaenoic (EPA, 20: 5ω3) and docosahexaenoic (DHA, 22: 6ω3) acids are highly unsaturated fatty acids, which are essential for organisms living at high latitudes (i.e., at low temperatures) because these fatty acids maintain fluidity and the optimal functioning of membranes [ 31 , 39 ].…”
Section: Introductionmentioning
confidence: 99%